2012
DOI: 10.1371/journal.pone.0043826
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin Causes G1 Arrest, Induces Apoptosis, and Enhances the Chemosensitivity to Gemcitabine in Pancreatic Cancer Cells

Abstract: Despite rapid advances in chemotherapy and surgical resection strategies, pancreatic cancer remains the fourth leading cause of cancer related deaths in the United States with a 5-year survival rate of less than 5%. Therefore, novel therapeutic agents for the prevention and treatment of pancreatic cancer are urgently needed. The aim of this study was to investigate the effect of pristimerin, a quinonemethide triterpenoid compound isolated from Celastraceae and Hippocrateaceae, on inhibition of cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 43 publications
(58 reference statements)
2
55
0
Order By: Relevance
“…In the gemcitabinesensitive HuCCT-1 cells, the anti-proliferative effect of gemcitabine led to G1 arrest through a reduction of cyclin d1. Although some studies have reported that gemcitabine could inhibit cell-phase transitioning during G1 phase (1,21), to date, there are no studies on cyclin d1 reduction as an anticancer effect of gemcitabine in CCC cells. This study revealed that gemcitabine induced a cell cycle arrest at the G0/G1 phase by reducing cyclin d1 levels in HuCCT-1 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In the gemcitabinesensitive HuCCT-1 cells, the anti-proliferative effect of gemcitabine led to G1 arrest through a reduction of cyclin d1. Although some studies have reported that gemcitabine could inhibit cell-phase transitioning during G1 phase (1,21), to date, there are no studies on cyclin d1 reduction as an anticancer effect of gemcitabine in CCC cells. This study revealed that gemcitabine induced a cell cycle arrest at the G0/G1 phase by reducing cyclin d1 levels in HuCCT-1 cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] So, the recovery of pristimerin from Celastrus orbiculatus has strong potential in pharmaceutical industry. The chemical structure of pristimerin is shown in Fig.…”
Section: )mentioning
confidence: 99%
“…The NF-kB DNA-binding activity was determined using the Trans-Am NF-kB /p65 ELISA Kit following the instructions outlined by the manufacturer and as described previously (4). Briefly, nuclear and cytosolic fractions were prepared from cells by using the Nuclear Extraction Kit following the instructions outlined by the manufacturer.…”
Section: Nf-kb Dna-binding Activity Assaymentioning
confidence: 99%
“…In the year 2013 in the United States alone, almost 45,220 men and women were diagnosed with pancreatic cancer and 38,460 died of disease (3). The poor prognosis of pancreatic cancer is mostly due to the lack of ability for early detection, the aggressive biologic behavior of the tumor and the insensitivity to chemotherapy (4). Gemcitabine, erlotinib, and abraxane are the only FDA-approved agents to treat pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%